Big data management and the Internet of things for improved health systems - Mishra, Brojo Kishore 1979-; Kumar, Raghvendra 1987- (IGI Global, Disseminator of Knowledge, 2018)
"This book explores a number of technologies can reduce overall costs for the prevention or management of chronic illnesses. These include devices that constantly monitor health indicators, devices that auto-administer therapies, or devices that track real-time health data when a patient self-administers a therapy. It also reviews mIoT and big data in healthcare fields"--Provided by publisher
Titel auf dem Cover: "Handbook of research on big data management and the Internet of things for improved health systems"
Keywords: Data Mining; Medical Informatics; Telemedicine; Cloud Computing; Telemetry; Internet; Data mining; Big data; Telecommunication in medicine; Cloud computing; Aufsatzsammlung